Problem-Based Learning In The Era Of Globalization: Developing Global Skills And Digital Literacy In Learners - Wibowo, Agung; Kurniawan, Hanif; Wulandari, Intan Ayu Idha; Balqis, Balqis; Nurhayati, Lilik (JURNAL PENDIDIKAN SAINS (JPS), 2025)
Education is a lifelong process to develop human potential optimally. Education also aims to form people with character, competence and competitiveness in the era of globalization. One of the competencies that students must have in the era of globalization is global skills and digital literacy. The aim of this study is to enhance global skills and digital literacy regarding the growth and development of living organisms among high school students through the implementation of the Problem-Based Learning (PBL) model. This research employs a classroom action research design with both quantitative and qualitative data analysis. The subjects of the study are students of class XI E-4 at SMA Negeri 3 Malang, consisting of 13 male and 21 female students. Data analysis yielded global skill scores of 84.75 (Cycle I) and digital literacy scores of 85.17 (Cycle I), and global skill scores of 88.28 (Cycle II) and digital literacy scores of 90.16 (Cycle II). The results of the statistical analysis using the t-test also show a significant difference in the global skills variable (0.026 < 0.05) and digital literacy (0.002 < 0.05) across both learning cycles. These results indicate an improvement in both global skills and digital literacy among the students. Based on the research findings, the implementation of the PBL model is deemed necessary as one of the efforts to address the globalization era, particularly in fostering the global skills and digital literacy of students.